PENINGKATAN KETERAMPILAN GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI LATIHAN DAN BIMBINGAN - juwariah, siti (Jurnal Dinamika Manajemen Pendidikan, 2020)
Teacher qualifications, even though they are bachelor, do not guarantee that each teacher is able to draw up a Learning Implementation Plan (RPP), as evidenced by the 8 teachers in SD Negeri Mojodanu II Ngombang District, Jombang, which are still 25% capable of preparing lesson plans independently, so supervision activities related to academic supervision in the preparation of the RPP . These conditions are influenced by: (1) teacher busyness, (2) lack of training and guidance as well as mentoring and (3) lack of socialization. Related to the above problems, there needs to be adequate handling assistance. In this case the effort made is to carry out training and guidance, which aims at improving teacher skills in the preparation of RPP according to SNP independently. Data analysis was carried out using qualitative descriptive analysis. The study was conducted in stages of the cycle, each cycle consisting of 4 (four) steps including: planning, implementation, observation and reflection. The results of this study, 8 teachers from schools that were the subjects of the study, all showed increased competency in accordance with established indicators of success. Suggestions proposed are: (1) it is necessary to intensify the improvement of teacher skills in preparing lesson plans through mentoring activities or the like (2) the need for means such as IHT, so that they can exchange experiences through academic dialogue